Spatial Economic Analysis of Manufacturing Firms Located in the Vicinity of Cape Town International Airport - Masilonyane Mokhele; Fradreck Garatsa (Urban Science, 2023)
Manufacturing activities are at the heart of contemporary capitalist economies, with observable geographical patterns of production. Debates about the interconnections between transportation technology advancements and land use acknowledge that airports can influence the spatial distribution of firms, including those involved in manufacturing. However, the manufacturing-related literature describes the land-use mix of airports and their surroundings without an in-depth spatial economic analysis of the firms positioned near airports. This study aimed to conduct a spatial economic analysis of manufacturing firms positioned in the environs of Cape Town International Airport, South Africa. Primary data were collected through survey interviews conducted with the representatives of 23 manufacturing firms situated in the environs of the airport. The study discovered the potential existence of a spatial cluster of manufacturing firms. This cluster is characterized by dense inter- and intraindustry linkages within the study area. It is recommended that planning authorities and other stakeholders augment the clustering of manufacturing firms in the vicinity of Cape Town International Airport, which comprises firms with direct and indirect linkages with the airport.